The Character of Moral Development - Boyd, Dwight (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 1989)
This paper analyzes the character implications of Kohlberg's conception of moral development combined with our current understanding of the moral point of view inherent in the most mature level of that development. The problem is first framed within an articulation of the most fundamental philosophical assumptions underlying Kohlberg's theory. Then the argument proceeds dialectically from correcting some of the common but mistaken character implications of the notion of principled morality to showing what positive picture of moral character emerges from an appreciation of recent elaborations of the nature of Stage Six. It is argued that certain dimensions of moral character are required by the performative sense of objectivity which operationalizes the notion of respect for persons forming the heart of Stage Six.